Fractional proportional derivative-based active disturbance rejection control of knee exoskeleton device for rehabilitation care - Nasir Ahmed Alawad; Amjad Jaleel Humaidi; Ahmed Sabah Alaraji (Institute of Advanced Engineering and Science, 2022)
The use of rehabilitation exoskeleton by physiotherapists in their daily practice is becoming more common. In this study, the active disturbance rejection controller (ADRC) is proposed to ensure high performance of trajectory tracking for asstitve exoskeleton at the level of knee-joint. The controlled medical robot has to mimic the actual physical training and application for knee-rehabilitation. Two versions of ADRC is presented to control the rehabilitation system. One version is based on conventional ADRC, while the other version is based on fractional proportional-derivative PD-ADRC. A comparison study in performance has been conducted between two versions of ADRCs in terms of robustness against disturbances. According to numerical simulations, the results showed that the fractional PD-based ADRC ouptperforms the ADRC in terms of robustness characteritics based on the index root mean square error (RMSE).